Evaluation of the electrochemical behavior of carbon paste electrode (CPE) with chalcopyrite (CuFeS2) in the presence of ferrous ions - Arena, F. A. [UNESP]; Bevilaqua, D. [UNESP]; Fujivara, C. S. [UNESP]; Benedetti, Assis Vicente [UNESP]; Guiliani, N.; Demergasso, C.; Quatrini, R.; Remonsellez, F.; DavisBelmar, C.; Levican, G.; Parada, P.; Barahona, C.; et al. (Trans Tech Publications Ltd, 2013)
In this work we present an electrochemical study using carbon paste electrode (CPE) with CuFeS2 in solutions with different concentrations of Fe2+ ions in order to evaluate the possible interaction between these ions and mineral sulfide in the absence and presence of the bacteria Acidithiobacillus ferroxidans.
Keywords: bioleaching; chalcopyrite; redox potential; electrochemistry